Productivity and profitability of rice hybrids at different nutrient management levels under semi-arid conditions of North Eastern Plains Zone - Raj, Rishi Raj; Yadav, M.P.; Kumar, Vikash (Annals of Agricultural Research, 2016)
The research work was undertaken at Student’s Instructional Farm, Chandra Sekhar Azad University of Agriculture and Technology, Kanpur, India, with the objective of identifying most suitable rice hybrid in terms of yield and economics, and work out the optimum nutrient management level for different rice hybrids. The experiment comprised 12 treatment combinations of 3 nutrient management levels viz. Farmer’s dose (80:30:30 N, P2 (RDF) (150:75:60:25 N, P2 O, ZnSO4 kg/ha) and 4 rice hybrids namely, PHB 71, Pro-agro 6444, PAC 832 and Shri Ram K2 Sonali. The experiment was conducted under split plot design with four replications. Hybrid PHB 71 produced significantly higher number of effective tillers, panicle length and grains per panicle as compared to Pro-agro 6444, PAC 832 and Shri Ram Sonali. The number of effective tillers, panicle length and grains per panicle increased significantly with increasing levels of nutrient management and maximised at 125% of RDF. Hybrid PHB 71 produced 6.5 t/ha grain yield which was computed to 8.4, 13.8 and 29.1% higher than the grain yield obtained from PAC 832, Pro-agro 6444 and Shri Ram Sonali, respectively. At 125 % of RDF the highest of 6.7 t/ha grain yield of rice was produced and recorded by 9.5 and 49.4% higher than the RDF and farmers dose, respectively. Gross return, net return and benefit: cost ratio were computed maximum in PHB 71 followed by PAC 832, Pro- agro 6444 and Shri Ram Sonali. At the same time gross return, net return and benefit: cost ratio were also obtained maximum at 125% of RDF as compared to RDF and farmers dose. , K2 O, ZnSO4 O5 , K2 O5 kg/ha) and 125% of RDF (187.5:93.75:75:31.25 N, P2 O kg/ha), Recommended dose of fertilisers